Chapter 5 China's Belt and Road Initiative through the lens of Central Asia - Vakulchuk, Roman (Routledge Studies on Asia in the World, 2019)
This chapter makes an empirical contribution by studying whether the launch of BRI has led to a shift in Central Asian attitudes towards and perceptions of China. We discuss the interaction between China and each of the five Central Asian states, highlighting local attitudes towards and perceptions of the big neighbour. We focus on economic interaction, infrastructure and education initiatives as they are among the main pillars of the BRI agenda, while acknowledging that cooperation on political, diplomatic, and security issues has been no less important for shaping perceptions of China in Central Asia. One limitation of our analysis should be mentioned. It is difficult to separate BRI analytically from other ongoing projects within the bilateral cooperation between China and the Central Asian countries, "as many bilateral agreements are now being brought under the Silk Road and BRI umbrella" (Dave 2018, p. 100). We attempt to overcome this limitation by tracing changes in attitudes towards and perception of China in general since 2013, when BRI was announced, and whether the change can be attributed to the promotion of BRI.